Long-term Overall Survival Outcomes in Patients with Early Stage, Peripherally Located, Non-small Cell Lung Cancer Treated with Stereotactic Ablative Radiotherapy in a Non-academic Cancer Centre. Issue 5 (May 2021) - Wood, A.; Aynsley, E.; Kumar, G.; Masinghe, S.; Anderson, M.; Veeratterapillay, J.; Huntley, C.; Blower, A.; Green, J.; Johnson, D.; Daniel, J.; Curtis, H.; et al.
Abstract: Aims: To report long-term outcomes of patients treated with stereotactic ablative radiotherapy (SABR) for early stage, peripherally located non-small cell lung cancer. Materials and methods: Data were collected retrospectively between September 2009 and May 2019. Electronic medical records were reviewed for baseline characteristics, treatment details and outcomes. All patients were treated according to local protocol based on the national UK SABR Consortium guidelines. Risk-adapted treatment schedules were used depending on the size and the location of the tumour (54 Gy in three fractions, 55 Gy in five fractions, 60 Gy in eight fractions or 50 Gy in 10 fractions). Overall survival outcomes were evaluated using the Kaplan–Meier method. Results: In total, 412 patients were included in the analysis. The median age was 76 years (range 48–93 years). Histological confirmation was obtained in 233 cases (56.6%). The median overall survival for all patients was 42.3 months (95% confidence interval 37.3–47.3 months), with 3- and 5-year overall survival of 52.8% and 37.3%, respectively. For biopsy-proven patients (56.6%), 3- and 5-year overall survival was 57.3% and 40.1%, respectively. With respect to overall survival, univariate and multivariate analysis revealed no significant difference in survival by technique (volume-modulated arc therapy versus conformal; three-dimensional computed tomography versus four-dimensional computed tomography), tumour location, smoking status at first contact, pre-treatment tumour stage or pre-treatment standardised uptake value. Survival was poorer for patients who received the 50 Gy in 10 fractions schedule. Treatment was very well tolerated with very low rates of grade 3–4 toxicity (1%). Conclusions: SABR for peripherally located, medically inoperable non-small cell lung cancer can be safely and effectively implemented in a non-academic institution with appropriate equipment and training. Overall survival outcomes and toxicity rates are comparable with internationally published studies. Patients treated with 50 Gy in 10 fractions had a poorer survival outcome. Highlights: SABR is the standard of care for medically inoperable, peripherally located non-small cell lung cancer. Excellent long-term overall survival outcomes achieved in major academic institutions can also be achieved in the non-academic setting. The roll out of SABR services by NHS England needs to be accompanied by appropriate training and quality assurance backing.